Spark plug
By bonding the discharge component with Ni and adding specific elements, the problem of easy cracking of the Ru discharge component is solved, and the durability and reliability of the spark plug are improved.
Patent Information
- Application Number
- CN202480003905.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-04-18
- Filing Date
- 2024-02-20
- Publication Date
- 2025-09-23
AI Technical Summary
The crystal structure of Ru is a close-packed hexagonal lattice, which has a large resistance to displacement due to external forces and is difficult to deform. Therefore, the discharge component mainly composed of Ru in the prior art is easily broken.
By joining the discharge component to a base material mainly composed of Ni, the value of the Vickers hardness of the fusion zone divided by the Vickers hardness of the discharge component is greater than 0.25 and less than 2.8, and elements such as Ir, Pt, Rh, Re, Pd, Mo, and W are added to the discharge component to enhance its mechanical strength.
The cracking of discharge components is reduced, and the durability and reliability of the spark plug are improved.
Smart Images

Figure CN120693756A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a spark plug including a discharge member containing Ru. Background Art
[0002] Patent Document 1 discloses a prior art in which a spark plug includes a first electrode including a discharge member and a second electrode facing the discharge member across a spark gap, wherein the discharge member is made of a metal containing Ru as a main component. Prior art literature Patent Literature
[0003] Patent Document 1: Japanese Patent Application Publication No. 2013-512551. Summary of the Invention Technical problem to be solved by the invention
[0004] The crystal structure of Ru is a close-packed hexagonal lattice, which has a large resistance to displacement due to external forces and is difficult to deform. Therefore, the conventional discharge component mainly composed of Ru has a problem of being easily broken.
[0005] The present invention has been made to solve the above-mentioned problem, and an object of the present invention is to provide a spark plug capable of reducing cracking of a discharge member. Means for solving technical problems
[0006] To achieve this object, a first embodiment of the present invention comprises: a first electrode including a discharge member joined to a base material composed mainly of Ni via a fusion zone; and a second electrode facing the discharge member across a spark gap, wherein the discharge member is composed mainly of Ru, and a value obtained by dividing the Vickers hardness of the fusion zone by the Vickers hardness of the discharge member is 0.25 to 2.8.
[0007] A second embodiment is a configuration according to the first embodiment, wherein the discharge member contains one or more elements selected from the group consisting of Ir, Pt, Rh, Re, Pd, Mo, W, Au, Al, Co, Ni, Cr, and Si.
[0008] A third aspect is the first aspect, wherein a value obtained by dividing the Vickers hardness of the fusion zone by the Vickers hardness of the discharge member is 1.05 or more and 2.8 or less.
[0009] A fourth aspect is the third aspect, wherein the discharge member contains one or more elements selected from the group consisting of Ir, Pt, Rh, Re, Pd, Mo, and W. Effects of the Invention
[0010] According to the present invention, the value obtained by dividing the Vickers hardness of the molten zone where the discharge member mainly composed of Ru is joined to the base material mainly composed of Ni by the Vickers hardness of the discharge member is 0.25 to 2.8. Therefore, deformation of the molten zone assists deformation of the discharge member, thereby reducing cracking of the discharge member. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 This is a one-side cross-sectional view of a spark plug according to an embodiment. Figure 2 It will Figure 1 FIG. 2 is an enlarged single-side cross-sectional view of the spark plug. FIG. DETAILED DESCRIPTION
[0012] Hereinafter, preferred embodiments of the present invention will be described with reference to the accompanying drawings. Figure 1 FIG. 1 is a one-side cross-sectional view of the spark plug 10 according to one embodiment, taken along the axis O. Figure 1 In FIG. 1 , the lower side of the paper is referred to as the front end side of the spark plug 10 , and the upper side of the paper is referred to as the rear end side of the spark plug 10 .
[0013] like Figure 1 As shown, the spark plug 10 includes a center electrode 13 (first electrode) and a ground electrode 19 (second electrode). An insulator 11 insulates the center electrode 13 from the ground electrode 19. The ground electrode 19 is connected to a metallic shell 18. The insulator 11 is a generally cylindrical member made of a ceramic such as alumina, which exhibits excellent mechanical properties and insulation properties at high temperatures. The insulator 11 is provided with an axial hole 12 extending therethrough along the axis O. The center electrode 13 (first electrode) is a rod-shaped conductor disposed in the axial hole 12 along the axis O.
[0014] Figure 2 It will Figure 1 Figure II shows a partially enlarged, one-side cross-sectional view of the spark plug 10. The center electrode 13 comprises a base material 14, a discharge member 15 disposed at the front end of the base material 14, and a molten zone 16 formed by melting the base material 14 and the discharge member 15. A core material with excellent thermal conductivity is embedded within the base material 14. The base material 14 is made of a metal primarily composed of nickel, and the core material is, for example, copper or an alloy primarily composed of copper. The core material may be omitted. A base material 14 primarily composed of nickel means that nickel accounts for 50% or more of the metal's mass.
[0015] The material of the discharge member 15 is a metal primarily composed of Ru. Ru primarily means that the mass of Ru accounts for at least 50% of the mass of the discharge member 15. In this embodiment, the discharge member 15 is disk-shaped. The discharge member 15 is secured to the base material 14 via a fusion zone 16 formed by laser welding, resistance welding, or the like.
[0016] return Figure 1 The terminal fitting 17 is a rod-shaped conductor connected to an ignition device (not shown), and its front end is disposed in the axial hole 12 of the insulator 11 . The terminal fitting 17 is electrically connected to the center electrode 13 in the axial hole 12 .
[0017] The metallic shell 18 is a generally cylindrical component that is fixed to a threaded hole in a tapping hole of an internal combustion engine (not shown). The metallic shell 18 is made of a conductive metal material (e.g., mild steel). The metallic shell 18 is fixed to the outer periphery of the insulator 11. A ground electrode 19 (second electrode), a rod-shaped conductor, is connected to the metallic shell 18. The ground electrode 19 bends from the metallic shell 18 toward the axis O.
[0018] like Figure 2 As shown, the ground electrode 19 comprises a base material 20 connected to the metallic shell 18, a discharge member 21 disposed within the base material 20, and a fusion zone 22 formed by melting the base material 20 and the discharge member 21. A core material with excellent thermal conductivity is embedded within the base material 20. The base material 20 is, for example, an alloy primarily composed of Ni, while the core material is made of Cu or an alloy primarily composed of Cu. The core material may be omitted.
[0019] Examples of materials for the discharge member 21 include noble metals such as Pt, Ir, Ru, and Rh, or W, which have higher spark consumption resistance than the base material 20, or alloys primarily composed of noble metals or W. The discharge member 21 is secured to the base material 20 via a fusion zone 22 formed by laser welding, resistance welding, or the like. A discharge surface 23 of the discharge member 15 of the center electrode 13, facing the distal end, faces the ground electrode 19 across a spark gap 24.
[0020] The spark plug 10 is manufactured, for example, by the following method. First, the center electrode 13 is inserted into the axial hole 12 of the insulator 11. Next, the terminal fitting 17 is inserted into the axial hole 12. After ensuring electrical continuity between the terminal fitting 17 and the center electrode 13, the metallic shell 18, to which the ground electrode 19 is pre-connected, is assembled onto the outer periphery of the insulator 11. The ground electrode 19 is bent to form a spark gap 24 between the center electrode 13 and the discharge member 21 of the ground electrode 19, thereby completing the spark plug 10.
[0021] In the center electrode 13, the value M / D (Vickers hardness M of the fusion zone 16 divided by the Vickers hardness D of the discharge member 15) is 0.25 or greater and 2.8 or less. The test surface for measuring the Vickers hardnesses M and D is a surface polished along a cross section including a straight line 26 passing through the center of gravity 25 of the discharge surface 23 of the discharge member 15 (a straight line 26 perpendicular to the discharge surface 23). The center of gravity 25 of the discharge surface 23 is the geometric center calculated using a known method when the discharge surface 23 is a planar figure.
[0022] Vickers hardness is calculated based on JIS Z2244-1:2020 by dividing the test force applied by the indenter's depression on the test surface by the surface area of the indenter. To account for variations, the Vickers hardness of the fusion zone 16 is calculated as the average of 30 random points on the test surface. The Vickers hardness of the discharge member 15 is calculated as the average of 30 random points on the test surface.
[0023] The discharge member 15 is manufactured by compressing and molding Ru-containing powder and sintering it at high temperature (sintering method). The sintering method allows the Vickers hardness of the discharge member 15 to be increased or decreased by adjusting the sintering temperature and pressure. The sintering method allows the discharge member 15 to be formed into any desired shape, such as a circular plate, a truncated cone, an elliptical cylinder, a triangular prism, a quadrangular prism, or other polygonal prisms.
[0024] The discharge member 15 can also be produced by plastic working such as hot or cold forging, rolling, swaging, punching, or wire drawing of an ingot of a metal material containing Ru. Plastic working can adjust the Vickers hardness of the discharge member 15 by increasing work strain (work hardening) and reducing grain size.
[0025] The molten zone 16 is produced by laser welding. Laser welding can increase or decrease the Vickers hardness of the molten zone 16 by varying the ratio of the base material 14 and the discharge member 15 in the molten zone 16 according to the laser output and the irradiation position of the laser beam. The molten zone 16 can also be produced by resistance welding. With resistance welding, the Vickers hardness of the molten zone 16 can be adjusted by adjusting the welding current, energization time, and applied pressure.
[0026] Ru has a close-packed hexagonal lattice structure, which has a high resistance to external force and is difficult to deform. Therefore, the discharge member 15 composed mainly of Ru is prone to cracking. When the value M / D (the Vickers hardness M of the molten zone 16 divided by the Vickers hardness D of the discharge member 15) is set to 0.25 or more and 2.8 or less, deformation of the molten zone 16 assists deformation of the discharge member 15, thereby reducing cracking of the discharge member 15 bonded to the base material 14 via the molten zone 16.
[0027] The Vickers hardness of the fusion zone 16 is preferably 100 HV to 650 HV, more preferably 120 HV to 630 HV. This is to ensure the tensile strength and toughness of the fusion zones 16 and 22 and reduce the possibility of breakage of the discharge member 15.
[0028] The Vickers hardness of the discharge member 15 is preferably 180 HV to 550 HV, more preferably 200 HV to 530 HV, in order to ensure the tensile strength and toughness of the discharge member 15 .
[0029] The discharge member 15 preferably contains, in addition to Ru, one or more elements selected from the group consisting of Ir, Pt, Rh, Re, Pd, Mo, W, Au, Al, Co, Ni, Cr, and Si. This is because the atomic radius of these elements is in the range of 111-144 pm, which is close to the atomic radius of Ru of 134 pm. Therefore, solid solution strengthening can improve the mechanical strength of the molten zone 16 formed by melting the base material 14 and the discharge member 15.
[0030] The discharge member 15 preferably contains, in addition to Ru, one or more elements selected from the group consisting of Ir, Pt, Rh, Re, Pd, Mo, and W. This is because the atomic radius of these elements is in the range of 130-139 pm, which is closer to the atomic radius of Ru of 134 pm, and thus the mechanical strength of the molten portion 16 can be further improved through solid solution strengthening.
[0031] In addition to Ru, the discharge member 21 may also contain oxides such as Y2O3 and Al2O3. The oxide content is, for example, 8% by mass or less. The combined proportion of elements other than Ru (excluding impurities) and oxides in the discharge member 21 is preferably 40% by mass or less. This is to prevent a decrease in the melting point of the discharge member 21. Examples of impurities include Na, K, Fe, Sn, Mn, Cu, Ag, and Th. The proportion of impurities in the discharge member 21 is, for example, less than 1% by mass. Example
[0032] The present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples.
[0033] (Fabrication of discharge components) Experimenters vacuum-dissolved a mixture of metals such as Ru, Ir, and Rh, and Y2O3 in varying proportions, and then used an inert gas atomization method to obtain various powders with varying Ru proportions. The powders were placed in a mold and compressed to form cylindrical compacts. The compacts were then sintered at approximately 2000°C in a reducing atmosphere. The sintering temperature and time were varied to produce discharge components with varying Vickers hardness. The discharge components were cylindrical, with a base diameter of 0.6 mm and a height of 0.55 mm. The density of the discharge components (based on the Archimedean method) was greater than 95%. The chemical composition of the discharge components was measured using a wavelength dispersive X-ray spectrometer (WDS). The measurement conditions were an accelerating voltage of 20 kV, a beam diameter of 20 μm, and a peak measurement time of 10 seconds.
[0034] (Preparation of test pieces) The testers laser welded the bottom surface of the discharge component to the bottom end of a base material consisting of a rectangular parallelepiped with a bottom width of 2.7 mm and a height of 1.3 mm, obtaining test pieces of sample No. 1-68 in which the discharge component was joined to the base material via a molten zone. The base material was nickel-based alloy NCF601. For example, the laser welding conditions for sample No. 61 were within the laser output range of 10-50 W. By varying the laser output and the irradiation position of the laser beam, the Vickers hardness of the molten zone of the test piece was varied. Thus, two test pieces of sample No. 1-68 each, each containing discharge components and molten zones of varying Vickers hardness, were obtained.
[0035] After embedding each test piece of Sample No. 1-68 in epoxy resin, the test surface was prepared by grinding a cross section along a line passing through the center of gravity of the bottom surface of the discharge member (a line perpendicular to the bottom surface). The discharge member and fusion zone on the test surface were examined using a metallurgical microscope to determine if there were any cracks.
[0036] (Determination of Vickers hardness) For test specimens confirmed for the presence of cracks, the Vickers hardness was determined by pressing an indenter into the test surface of the fusion zone and the discharge component with a test force of 500 N for 10 seconds in accordance with JIS Z2244-1:2020. The average Vickers hardness of 30 random points on the test surface of the fusion zone was taken as the Vickers hardness M of the fusion zone, and the average Vickers hardness of 30 random points on the test surface of the discharge component was taken as the Vickers hardness D of the discharge component. The value M / D was calculated by dividing the Vickers hardness M of the fusion zone by the Vickers hardness D of the discharge component.
[0037] (Hot and cold cycle test) After assembling a metallic shell with a ground electrode attached to the outer periphery of an insulator, onto which a center electrode and terminal fittings, each of the test pieces of sample No. 1-68, were attached, the ground electrode was bent to produce spark plug samples with a spark gap between the ground electrode and the discharge element of the center electrode. The materials and dimensions of the spark plug samples were identical, except for the test pieces.
[0038] The testers installed the sample in a 2-liter four-cylinder direct-injection engine with a supercharger and repeatedly ran the engine at 5000 rpm for one minute, then at 800 rpm for one minute, for a total of 100 hours of hot and cold cycle testing.
[0039] After the thermal cycling test, the sample specimens were embedded and fixed in epoxy resin. A cross section along a line passing through the center of gravity of the bottom surface of the discharge component (a line perpendicular to the bottom surface) was polished, and the presence of cracks in the discharge component and the fusion zone was examined using a metallurgical microscope.
[0040] Samples with cracks after laser welding were rated C. Samples without cracks after laser welding but with cracks after thermal cycling were rated B. Samples without cracks after both laser welding and thermal cycling were rated A.
[0041] The chemical composition, Vickers hardness M, D, value M / D, and evaluation of the discharge components of Sample No. 1-68 are shown in Tables 1 and 2. The chemical composition of each sample is shown in Tables 1 and 2, with Ru as Bal (balance), and the proportions (mass %) of added elements other than Ru, excluding impurities.
[0042]
[0043]
[0044] As shown in Tables 1 and 2, Sample No. 1, which had an M / D value of 0.24, and Sample No. 68, which had an M / D value of 2.90, were judged as C. It is presumed that the deformation of the molten zone failed to assist the deformation of the discharge member, and that the discharge member was ruptured due to the tensile stress in the discharge member caused by the rapid heating and cooling during welding and the contraction of the molten zone.
[0045] In contrast, sample No. 2-67, whose M / D value was 0.25 or more and 2.80 or less, was judged as A or B. This is presumably because the tensile stress of the discharge member caused by the rapid heating and cooling during welding and the contraction of the molten zone was reduced by the molten zone, and therefore the discharge member and the molten zone did not break during welding.
[0046] In particular, sample No. 34-67, whose M / D value was 1.05 or more and 2.80 or less, was judged as A. It is understood that when the M / D value is within this range, the discharge member and the fusion zone will not be broken even when subjected to thermal shock during the thermal cycle test.
[0047] Sample No. 34-67, which was judged as A, contained elements selected from the group consisting of Ir, Pt, Rh, Re, and Pd in addition to Ru. The reason for being judged as A is presumably because the strength of the molten portion was improved by solid solution strengthening by these elements.
[0048] As mentioned above, although this invention was demonstrated based on embodiment, this invention is not limited to the said embodiment at all, It can be easily estimated that various improvements and modifications can be made without departing from the scope of this invention.
[0049] In the embodiment, the center electrode 13 is exemplified as the first electrode, and the ground electrode 19 is exemplified as the second electrode, but this is not necessarily limited to these examples. Of course, the ground electrode 19 can be used as the first electrode, and the center electrode 13 can be used as the second electrode. In this case, the discharge member 21, which is primarily composed of Ru, is fixed to the base material 20, which is primarily composed of Ni, of the ground electrode 19 via a fusion zone 22. The value obtained by dividing the Vickers hardness of the fusion zone 22 by the Vickers hardness of the discharge member 21 is set to be 0.25 or higher and 2.8 or lower.
[0050] While the embodiment describes a case where the base member 20 of the ground electrode 19 is curved, this is not necessarily the case. A straight base member may be used instead of the curved base member 20. In this case, the front end of the metallic shell 18 is extended in the axial direction, the straight base member is connected to the metallic shell 18, and the ground electrode 19 is positioned facing the center electrode 13. The number of ground electrodes 19 can also be appropriately determined.
[0051] In the embodiment, the ground electrode 19 is described as being arranged so that the discharge member 15 and the ground electrode 19 face each other in the axial direction. However, this is not necessarily limited to this, and the positional relationship between the ground electrode 19 and the center electrode 13 can be appropriately set. Other examples of positional relationships between the ground electrode 19 and the center electrode 13 include arranging the ground electrode 19 so that the side surface of the discharge member 15 of the center electrode 13 faces the ground electrode 19.
[0052] In the embodiment, the discharge member 21 is fixed to the rear end surface of the base material 20 of the ground electrode 19, but the present invention is not necessarily limited to this. As long as the spark gap 24 is provided between the discharge member 21 and the center electrode 13, the discharge member 21 can be fixed to any surface of the base material 20. The discharge member 21 can also be omitted from the ground electrode 19. Description of Reference Numerals
[0053] 10 spark plugs 13 Center electrode (first electrode) 14 base material 15 discharge components 16 Melting section 19 ground electrode (second electrode) 24 spark gap.
Claims
1. A spark plug comprising: The first electrode includes a discharge member joined to a base material mainly composed of Ni via a fusion zone; and The second electrode faces the discharge component across the spark gap. The discharge component is mainly composed of Ru, A value obtained by dividing the Vickers hardness of the fusion portion by the Vickers hardness of the discharge member is 0.25 or more and 2.8 or less.
2. The spark plug according to claim 1, wherein The discharge member contains one or more elements selected from the group consisting of Ir, Pt, Rh, Re, Pd, Mo, W, Au, Al, Co, Ni, Cr, and Si.
3. The spark plug according to claim 1, wherein The value is 1.05 or more and 2.8 or less.
4. The spark plug according to claim 3, wherein: The discharge member contains one or more elements selected from the group consisting of Ir, Pt, Rh, Re, Pd, Mo, and W.
Citation Information
Patent Citations
Electrode materials for spark plugs
JP2013512551A